Detection of Leptospiral Antibodies in Rodents and Shrews in Human Residence Vicinity in Kilwa District: A Potential Public Health Risk - Mathayo Cralency Kikoti; Athumani Msalale Lupindu; Abdul S. Katakweba (Journal of Applied Veterinary Science And Technology, 2025)
Background: Leptospirosis is a worldwide neglected zoonotic infection that affects both humans and animals in tropical and subtropical countries. Purpose:  The objective of this study was to determine the presence of leptospiral antibodies in rodents and shrews, as evidence of public health threat. Method: Sera from 202 rodents and shrews were prepared and tested against five live antigens to detect leptospiral antibodies by using microscopic agglutination test. Leptospiral serovars commonly reported in Tanzania namely; Sokoine, Pomona, Hebdomadis, Lora, and Grippotyphosa were used in this study. Face-to-face interviews about cause, clinical signs, transmission, treatment and risk practices were conducted.  Results: The overall prevalence of leptospiral antibodies in rodents and shrews was 14.36% (95% CI:0.0983-0.1996), whereby mastomys natalensis was a more predominant positive host species. Serovar Sokoine was more prevalent compared to other tested serovars. The antibody titers obtained in this study ranged from 1:20 to 1:80, which suggests a long-standing exposure of rodents and shrews to different leptospiral serovars. Awareness of respondents about leptospirosis was below 50% in all aspects of enquiry.  Conclusion: Given the human economic activities and the ecology of rodents and shrews in study area, the findings of this study suggest a public health threat. Therefore, rodents and shrews control should be encouraged but also  public and institutional efforts to prevent outbreaks are recommended.